Self-reported adherence to anticoagulation and its determinants using the Morisky medication adherence scale. Issue 4 (October 2015) - Castellucci, Lana A.; Shaw, Joseph; van der Salm, Katrien; Erkens, Petra; Le Gal, Gregoire; Petrcich, William; Carrier, Marc
Abstract: Background: Direct oral anticoagulants (DOACs) are used for treatment of venous thromboembolism (VTE) and stroke prevention in atrial fibrillation (AF). Given the shorter half-life and lack of laboratory monitoring compared to vitamin-K antagonists (VKAs), adequate adherence to DOACs is important. Reported anticoagulation adherence is unclear in clinical practice. Objectives: To assess self-reported anticoagulation adherence in a tertiary center anticoagulation clinic. Patients/Methods: Cross-sectional study of patients on oral anticoagulants (VKAs, rivaroxaban, dabigatran and apixaban). Anticoagulation adherence was assessed using the 4-item Morisky score. Baseline characteristics were evaluated for association with adherence. Results: Five hundred patients completed the survey; 74% were on VKAs and 26% on DOACs: rivaroxaban 102 (79%); dabigatran 26 (19%); apixaban 2 (2%). Main indications for anticoagulation were VTE (72%) and AF (18%). Self-reported anticoagulation adherence using the 4-item Morisky scale was 56.2% for patients on VKAs and 57.1% for patients on DOACs. Predictors of anticoagulation adherence were age (OR = 1.02; 95% CI:1.01-1.03), female gender (OR = 1.58; 95% CI:1.10-2.27), use of additional oral medications (OR = 2.78; 95% CI:1.67-4.63), and retired employment status (OR = 2.31; 95% CI:1.51-3.55). In backward selection multivariate analyses age, female gender and use of other oral medications remained significantly associated with anticoagulation adherence. Conclusions: Self-reported anticoagulation adherence was similar between VKAs and DOACs. Until laboratory assays are universally available to evaluate DOAC adherence, physicians should emphasize the importance of anticoagulation adherence at each patient encounter. The Morisky scale provides simple assessment of anticoagulation adherence; however it has not yet been validation for this purpose. Highlights: Adherence rates were similar for patients on DOACs and VKAs and reported at 55% There were no differences in adherence rates for once or twice daily anticoagulants Predictors for good adherence were age, female gender, use of other oral medications